A importância do estudo da cavitação em turbomáquinas hidráulicas: bombas centrífugas e turbinas hidráulicas. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
Much of the electricity consumed in the country comes from hydroelectric plants, with a significant and growing energy demand. To meet the energy demands hydroelectric plants are working at the maximum limit, favoring the appearance of problems of various kinds, such as cavitation. This process produces negative consequences in hydraulic equipment such as noise, vibration of structures, reducing power and equipment efficiency, instability in the flow of the fluid and the most aggravating: erosion, which is one of the most harmful diseases that occur in the hydraulic equipment, due cause structural problems and economic losses due to leave dead machines periodically for repair, maintenance and even partial or complete replacement of the equipment .. in general, turbomachinery, because the free movement of bubbles immersed in the fluid flowing the internal channels of the same, are vulnerable to cavitation because it can occur in any area of the structure or the blades. The study aimed to identify techniques for analysis and monitoring of cavitation in hydraulic machines as an example, we can mention: the acoustic method involving sound measurement by means of sensors and preamplifiers, which propagates in the fluid transmitting its energy acoustic structure, thereby enabling the measurement of sound with those data it holds a supervisory equipment, the analysis also can prevent the development or expansion of the phenomenon; Another method is the vibration that occurs by monitoring the signals obtained by sensors energy associated with the vibration process which transforms the sensors mechanical vibration energy into electrical signals, with the data obtained it is possible to make comparisons with plants or earlier and thus identify if there were any new dynamic effort. In addition, measures can be taken in the system design phase. The pumps, the calculation of NPSH makes a prediction of the safety margin against the effects of cavitation. Can prevent the occurrence of erosion, it is necessary to keep the equipment in operating conditions around its design point. In the event of cavitation erosion, the welding process can recover the damaged parts, filling the holes and reconstituting the contours. It is important to make frequent maintenance at the right time, noting that a slightly higher cost in the design phase will save a lot of hard work and maintenance cost.
Keywords: Energia elétrica; Turbomáquinas; Cavitação; Erosão; CNPQ::CIÊNCIAS EXATAS E DA TERRA